Assessing awareness in severe Alzheimer’s disease - Huntley, Jonathan; Bor, Daniel; Deng, Feng; Mancuso, Marco; Mediano, Pedro A. M.; Naci, Lorina; Owen, Adrian M.; Rocchi, Lorenzo; Sternin, Avital; Howard, Robert (Frontiers in Human Neuroscience, 2023)
There is an urgent need to understand the nature of awareness in people with severe Alzheimer’s disease (AD) to ensure effective person-centred care. Objective biomarkers of awareness validated in other clinical groups (e.g. anaesthesia, minimally conscious states) offer an opportunity to investigate awareness in people with severe AD. In this paper we demonstrate the feasibility of using Transcranial magnetic stimulation (TMS) combined with EEG, event related potentials (ERPs) and fMRI to assess awareness in severe AD. TMS-EEG was performed in 6 healthy older controls and 3 people with severe AD. The perturbational complexity index (PCIST) was calculated as a measure of capacity for conscious awareness. People with severe AD demonstrated a PCIST around or below the threshold for consciousness, suggesting reduced capacity for consciousness. ERPs were recorded during a visual perception paradigm. In response to viewing faces, two patients with severe AD provisionally demonstrated similar visual awareness negativity to healthy controls. Using a validated fMRI movie-viewing task, independent component analysis in two healthy controls and one patient with severe AD revealed activation in auditory, visual and fronto-parietal networks. Activation patterns in fronto-parietal networks did not significantly correlate between the patient and controls, suggesting potential differences in conscious awareness and engagement with the movie. Although methodological issues remain, these results demonstrate the feasibility of using objective measures of awareness in severe AD. We raise a number of challenges and research questions that should be addressed using these biomarkers of awareness in future studies to improve understanding and care for people with severe AD.